2007
DOI: 10.1007/s00109-007-0283-1
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing hypoxic adaptation to prevent, treat, and repair stroke

Abstract: The brain demands oxygen and glucose to fulfill its roles as the master regulator of body functions as diverse as bladder control and creative thinking. Chemical and electrical transmission in the nervous system is rapidly disrupted in stroke as a result of hypoxia and hypoglycemia. Despite being highly evolved in its architecture, the human brain appears to utilize phylogenetically conserved homeostatic strategies to combat hypoxia and ischemia. Specifically, several converging lines of inquiry have demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 58 publications
(50 reference statements)
1
61
0
Order By: Relevance
“…To date most research has concentrated on the cellular adaptation that requires long-tem adaptive changes including gene expression changes, which involve transcription factors [48].…”
Section: Tnf-α and Hypoxia In The Cnsmentioning
confidence: 99%
“…To date most research has concentrated on the cellular adaptation that requires long-tem adaptive changes including gene expression changes, which involve transcription factors [48].…”
Section: Tnf-α and Hypoxia In The Cnsmentioning
confidence: 99%
“…It is thought that the consequences of inadequate tissue oxygenation, such as seen in anemia, stroke, and ischemic cardiovascular diseases, might be mitigated by increased levels of HIF (9), and therefore, pharmacologic inhibitors of EGLN prolyl hydroxylase activity might have therapeutic benefits. Preclinical studies have shown that prolyl hydroxylase inhibitors are useful for treatment of anemia (10) and may protect against ischemic renal disease (11), myocardial infarction (12), stroke (13), and whole body hypoxia (14).…”
mentioning
confidence: 99%
“…Recent studies indicate that Epo, vascular endothelial growth factor and SDF-1 are transcriptionally regulated by hypoxia via the transcriptional activator hypoxia-inducible factor 1. 6 These findings suggest that neurogenesis, angiogenesis and chemotaxis of new born neurons into the injury site can be potentially regulated by a drug that stabilized hypoxia-inducible factor 1. Indeed, studies from a number of groups have identified small molecule activators of the hypoxia-inducible factor pathway that are ripe for testing in this context.…”
Section: Giving the Brain A Push: Epo Sdf-1 Angiogenesis And Beyondmentioning
confidence: 99%
“…Indeed, studies from a number of groups have identified small molecule activators of the hypoxia-inducible factor pathway that are ripe for testing in this context. 6 Some of these drugs are already in phase II human clinical trials for other diseases and could be tested in preclinical recovery studies within the year.…”
Section: Giving the Brain A Push: Epo Sdf-1 Angiogenesis And Beyondmentioning
confidence: 99%